Contributions of domain-related phenomena on dielectric constant of lead-based ferroelectric ceramics under uniaxial compressive pre-stress - Rattikorn Yimnirun (2018)
The dielectric constant of lead-based ferroelectric ceramics in three different systems, i.e. BT-PZT, PMN-PT and PMN-PZT, was measured under uniaxial compressive pre-stress to investigate the contributions of different domain-phenomena. The dielectric constant was observed at room temperature under the compressive pre-stress up to 15 MPa, 22 MPa and 5 MPa for BT-PZT, PMN-PT and PMN-PZT, respectively, using a homebuilt uniaxial compressometer. Dielectric constant of the BT-PZT ceramics increased significantly with increasing applied stress. Larger changes in the dielectric constant with the applied stress were observed in the PZT-rich compositions. However, for PMN-PT and PMN-PZT ceramic systems, changes in the dielectric constant with the stress were found to depend significantly on the ceramic compositions. The experimental results could be explained by both intrinsic and extrinsic domain-related mechanisms involving domain wall motions, as well as the de-aging phenomenon from the application of the compressive pre-stress. Roles of different types of domains, i.e. micro-domains and nano-domains, were also discussed. © World Scientific Publishing Company.